2014
DOI: 10.1186/2251-6581-13-32
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life in diabetic patients: comparison of the Persian version of Geriatric Oral Health Assessment Index and Oral Health Impact Profile: A descriptive-analytic study

Abstract: BackgroundDiabetes mellitus is one of the systemic disease which is show important oral manifestation and influence oral health. This study describes how diabetes mellitus affects oral health and oral health-related quality of life. The aim of this study was to evaluate the oral health and oral health-related quality of life of diabetic patients and compare the discriminative capability of Persian versions of two GOHAI and OHIP-14 questionnaires in these patients.MethodsA total of 350 patients with Type II dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 26 publications
(39 reference statements)
7
53
1
Order By: Relevance
“…A previous study involving 350 patients with diabetes showed that those who had dry mouth had more missing teeth. Moreover, in a study by Sandberg et al ., dry mouth was significantly associated with diabetes even after stratification for the medications taken.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study involving 350 patients with diabetes showed that those who had dry mouth had more missing teeth. Moreover, in a study by Sandberg et al ., dry mouth was significantly associated with diabetes even after stratification for the medications taken.…”
Section: Discussionmentioning
confidence: 95%
“…The GOHAI was used to evaluate the OHRQoL (Tubert-Jeannin et al, 2003). This brings the patient's daily experience to the forefront (Blaizot et al, 2013) and provides the possibility to determine functional problems, discomfort and pain (Nikbin, Bayani, Jenabian, Khafri, & Motallebnejad, 2014). In fact, several studies have established a link between diabetes and low OHRQoL (Azogui-Lévy et al, 2018;Nikbin et al, 2014;Sadeghi, Taleghani, & Farhadi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This brings the patient's daily experience to the forefront (Blaizot et al, 2013) and provides the possibility to determine functional problems, discomfort and pain (Nikbin, Bayani, Jenabian, Khafri, & Motallebnejad, 2014). In fact, several studies have established a link between diabetes and low OHRQoL (Azogui-Lévy et al, 2018;Nikbin et al, 2014;Sadeghi, Taleghani, & Farhadi, 2014). Periodontitis is known to affect OHRQoL by increasing the severity and extent of periodontal disease (Buset et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to xerostomia, oral health‐related quality of life (OHRQoL) was assessed by Oral Health Impact Profile‐14 questionnaire (OHIP‐14) (Navabi, Nakhaee, & Mirzadeh, ; Slade, ). Among oral‐specific means, the OHIP is presently one of the most comprehensive measures of the impact of oral condition on health‐related quality of life (Allen & McMillan, ; Nikbin, Bayani, Jenabian, & Motallebnejad, ; Slade & Spencer, ; Vikram & Singh, ). This questionnaire contains 14 questions and examines the effect of oral health on daily physical, psychological, and social behavior of people.…”
Section: Methodsmentioning
confidence: 99%